The WorldatWork handbook of compensation, benefits & total rewards : a comprehensive guide for HR professionals - WorldatWork (Organization) (Hoboken, N.J. : John Wiley & Sons, 2007)
"The WorldatWork Handbook of Compensation, Benefits, and Total Rewards is a comprehensive tool for recruiting, rewarding, and retaining talent in the twenty-first century. With its special focus on structuring and implementing a total rewards program, this is a fully modern guide to compensation."--Jacket
Introduction : redefining employee rewards / Anne C. Ruddy -- 1. Total rewards : everything that employees value in the employment relationship -- 2. Why the total rewards approach works -- 3. Developing a total rewards strategy -- 4. Designing a total rewards program -- 5. Communicating total rewards -- 6. Compensation fundamentals -- 7. Regulatory environment : the FLSA and other laws that affect compensation practices -- 8. Market pricing -- 9. Salary surveys : a snapshot -- 10. Job analysis, documentation, and evaluation -- 11. Base pay structures -- 12. Sales compensation fundamentals -- 13. Executive compensation : an introduction -- 14. Linking pay to performance -- 15. Cash bonus plans and recognition programs -- 16. Equity-based rewards -- 17. Employee benefits basics -- 18. Benefits compliance : an overview for the HR professional -- 19. Worker privacy, unpaid leave, and other benefit-related laws that protect the individual -- 20. Planning benefits strategically -- 21. Implementing flexible benefits -- 22. Work-life effectiveness -- 23. Caring for dependents -- 24. Culture at work.
Includes bibliographical references (pages 821-825) and index.
Print version record.
John Wiley and Sons
Keywords: Compensation management -- Handbooks, manuals, etc; Salaires -- Gestion -- Guides, manuels, etc; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Human Resources & Personnel Management; Compensation management; Electronic books; Handbook; handbooks; Handbooks and manuals; Handbooks and manuals; Guides et manuels